2010
DOI: 10.1161/circresaha.110.221168
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Activator of Nuclear Factor κB Ligand Is a Novel Inducer of Tissue Factor in Macrophages

Abstract: Rationale: Although recent studies have suggested a role for the receptor activator of nuclear factor B ligand (RANKL) in the late stages of atherosclerosis (eg, plaque destabilization and rupture), the underlying mechanisms and subsequent events are unclear.Objective: Because blood clotting is common after plaque rupture, we hypothesized that RANKL influenced tissue factor (TF) expression and activity to initiate the coagulation cascade. Key Words: receptor activator of nuclear factor-B ligand Ⅲ tissue factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For example, RANKL induces MCP-1 expression and secretion and matrix MMP activity in SMCs (122). In addition, RANKL induces TF expression in macrophages mainly through the cooperative action of NF-κB, AP-1, and Egr-1, supporting a role of RANKL in the thrombogenicity of atherosclerotic plaques (123). Furthermore, RANK, RANKL, and the decoy receptor for RANKL osteoprotegerin (OPG) have been related with vascular calcification, a crucial step for plaque destabilization and rupture.…”
Section: Other Tnf Superfamily Members Implicated In Atherothrombosismentioning
confidence: 90%
“…For example, RANKL induces MCP-1 expression and secretion and matrix MMP activity in SMCs (122). In addition, RANKL induces TF expression in macrophages mainly through the cooperative action of NF-κB, AP-1, and Egr-1, supporting a role of RANKL in the thrombogenicity of atherosclerotic plaques (123). Furthermore, RANK, RANKL, and the decoy receptor for RANKL osteoprotegerin (OPG) have been related with vascular calcification, a crucial step for plaque destabilization and rupture.…”
Section: Other Tnf Superfamily Members Implicated In Atherothrombosismentioning
confidence: 90%
“…Previous studies have shown that RANKL induces the secretion of proinflammatory cytokines through the activation of the p38 MAPK, JNK, ERK, and NF-κB pathways (Kim et al, 2010;Riegel et al, 2012;Seshasayee et al, 2004). Moreover, PI3K activates intracellular calcium levels, and its blocking by Wortmannin inhibits antigen-mediated mast cell degranulation and cytokine production in both rodent and human mast cells (Okayama et al, 2003).…”
Section: Regulatory Effect Of Dexamethasone In Rankl-induced Inflammentioning
confidence: 99%
“…Importantly, pre-incubation with statins has been shown to reduce ERK 1/2 phosphorylation and associated pro-inflammatory functions in response to C-reactive protein (CRP) in human monocytes [51]. Confirming the pro-inflammatory relevance of ERK activation, recent findings also indicate that ERK1/2 pathway is crucial for pro-thrombotic in vitro activities of receptor activator of nuclear factor κB ligand (RANKL) in macrophages [52]. Accordingly, we recently showed that that ERK1/2 activation is pivotal for the neutrophilic release of matrix metalloproteases (MMPs) in response to RANKL [53].…”
Section: The Role Of Mitogen-activated Protein Kinases (Mapks)mentioning
confidence: 99%